2020
DOI: 10.1007/s12526-020-01043-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Acartia tonsa Dana, 1849 (Calanoida: Copepoda) and phylogenetic reconstruction of the genus Acartia Dana, 1846

Abstract: The calanoid copepod, Acartia tonsa Dana, 1849 is one of the most abundant and well-studied estuarian species with a worldwide distribution. In this research, we use the mitochondrial cytochrome oxidase subunit I gene to study the phylogeography of A. tonsa by analyzing sequences from specimens collected in the western Gulf of Mexico (GOM) along with all sequences from previous research. We reconstruct the phylogeny for the genus Acartia Dana, 1846 and highlight numerous potential misidentifications of Acartia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…With these rates, all the three pairs of cryptic species in our data would have diverged already in the Miocene, from 6 to 26 Ma (Table 7). While this appears unexpected in the context of European biogeography, in the context of copepod systematics these estimates are not exceptional: similar or even deeper cryptic lineages are frequently observed [20,21,26,44,45,[89][90][91]104,105]. Several studies on the phylogeography of freshwater copepods (including European populations) have pointed to the Early Miocene as a possible time of initial divergence [21,26,76].…”
Section: Age Of Diversitymentioning
confidence: 92%
See 2 more Smart Citations
“…With these rates, all the three pairs of cryptic species in our data would have diverged already in the Miocene, from 6 to 26 Ma (Table 7). While this appears unexpected in the context of European biogeography, in the context of copepod systematics these estimates are not exceptional: similar or even deeper cryptic lineages are frequently observed [20,21,26,44,45,[89][90][91]104,105]. Several studies on the phylogeography of freshwater copepods (including European populations) have pointed to the Early Miocene as a possible time of initial divergence [21,26,76].…”
Section: Age Of Diversitymentioning
confidence: 92%
“…It should be noted that copepod populations also overall show extreme mitochondrial DNA diversity [90]. Interestingly, this is not only for geographically isolated freshwater populations, but also for marine species, where populations from relatively close locations can demonstrate high variability [11,20,[44][45][46][47]50,[86][87][88][89][90][91][92]. These "intra-species" levels are extraordinary in comparison with vertebrate and invertebrate taxa, which commonly show <3% intraspecific and >2% interspecific variation [93][94][95].…”
Section: Cryptic Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…COI barcode reference sequences are available for many-if not most-of the more abundant and/or ecologically important species from coastal ocean areas, as well as surface layers (epipelagic zone) of the open ocean. Additional effort is needed for taxonomically challenging taxa, including species of the genus Acartia (Figueroa et al 2020) and family Paracalanidae (Cornils and Held 2014;Moon et al 2010), as well as representatives of bathy-and abyssopelagic taxa, which remain under-sampled. Rapid progress is being made with COI barcoding of copepods.…”
Section: Copepodamentioning
confidence: 99%
“…Among neritic Acartia copepods, A. tonsa also has a wide geographical distribution and different life history strategies including diapausing egg production pro-cesses, in each habitat (Caudill & Bucklin 2004, and citations therein). Molecular techniques revealed that A. tonsa has experienced geographical isolation resulting in the divergence of multiple, distinct cryptic lineages (Caudill & Bucklin 2004, Chen & Hare 2011, Costa et al 2014, Figueroa et al 2020). The results of these studies indicate the possible presence of cryptic species also in A. steueri, and molecular biological methods are considered to be extremely useful for elucidating the diversity of life histories in this copepod.…”
Section: Timing Of Diapausing Egg Productionmentioning
confidence: 99%